Pengembangan E- Diagnostic Four Tier Test Untuk Mengidentifikasi Miskonsepsi Peserta Didik - Jannah, Raudhatul; Rahmi, Indriati (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2020)
Research has been conducted on the development of the e-diagnostic four-tier test to identify misconceptions of students from SMAN 9 Sijunjung. The research method used is Research and Development (R&D) using the ADDIE model. The research was conducted at SMAN 9 Sijunjung in class XI MIPA 2. The validity test of the E-Diagnostic Four Tier physics test was given to 5 expert validators assessed from the aspect of material, construction, misconception and language, practicality test was given to 1 physics educator and 20 people students and effectiveness tests were tested on 20 students. The results of the validity test analysis by the expert validator showed that the E-diagnostic test in the form of Four-tier test developed was very valid with an average of 82.4%, the results of the practicality analysis by educators and students were very practical with an average of 81.65%, while the results of the effectiveness analysis for the product obtained a question validity of 70% with a valid category. reliability of the question 0.88 with a reliable category, the level of difficulty and different power of a good question each item, while the analysis of misconceptions obtained a percentage of 63% in the material of thermodynamics and 55.5% in the material of optical devices. This shows that the E-Diagnostic Four Tier Test physics test is categorized as very valid and very practical to use in learning physics